E-tutoring system for primary 6 mathematics - Chen, Ping (2017)
This report presents the creation and implementation of E-tutoring learning management system for primary 6 mathematics named “Whiteboard”. It also describes the experience gain from doing this project. Through development of the system to make it a more suitable tutoring system for primary 6 mathematic learning. The project was carried out in 4 stages: research and function analysis, design, implementation of the functions and then Testing. Features that is relevant to the project objective has been of great important to this project. Screenshots of the functions and work flows are also presented in this report.